Inspiration from table tennis racket: Preparation of rubber-wood-bamboo laminated composite (RWBLC) and its response characteristics to cyclic perpendicular compressive load. (1st June 2020) - Deng, Jianchao; Wei, Xin; Zhou, Haiying; Wang, Ge; Zhang, Shuangbao
Graphical abstract: Highlights: Rubber acted as a "bodyguard" within rubber-wood-bamboo laminated composite (RWBLC). The table tennis racket "design" offered great damping & anti-deformation properties. Bamboo suffered more severe invalidation of bearing units than wood at 260 °C. Only RPPBPPR structure can bear ten cycles of perpendicular compression at 260 °C. Abstract: Inspired by table tennis racket, ten assembly patterns of 7-ply rubber-wood-bamboo laminated composites (RWBLCs) were prepared, and physical, static destructive mechanics and pendulum impact tests were conducted, seeking for the possibility of rubber protecting natural biomass material, for better performance in the area of construction and transportation. The response of RWBLCs to cyclic perpendicular compressive load and its sensitivity to temperature (140, 170, 200, 230, 260 °C) were analyzed. Results indicated that RWBLCs' density raised as the proportion of rubber increased, however hardly affect the lightweight design of laminated biomass composites. The structure PPPPPPP performed the poorest underwater dimensional stability, while the opposite for RPPRPPR and PRPRPRP. The RWBLCs RPPPPPR, RPPBPPR and RPBBBPR, had superior bending, shearing, and pendulum impact capacity. Synthesis analysis of load–displacement curves, thickness decrement and energy change implied that "table tennis racket" structures (RPPPPPR, RPPRPPR, RPPBPPR, RPBBBPR, RPBB′BPR) achieved great damping aseismic performance and above-average deformation resistance. As temperature increased, the degree of crystallinity of wood and bamboo experienced a slight rise and distinct fall within 140~200 °C and 230~260 °C, respectively. Besides, biomass material suffered evident pyrogenic decomposition of cellulose and lignin at 260 °C that RWBLCs could not withstand whole ten cycles of perpendicular compression, except RPPBPPR.